CLASSIFICATION OF PHONETIC AND PHONOLOGICAL UNITS IN WORLD LINGUISTICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article contains opinions on the classification of phonetic and phonological units in world linguistics, its implementation by representatives of different schools of linguistics at different levels and directions. It also provides an analysis of different points of view on this issue and expresses a reaction to them.